Combinational Recommendation of Vaccinations, Mask-Wearing, and Home-Quarantine to Control Influenza in Megacities: An Agent-Based Modeling Study With Large-Scale Trajectory Data - Zhang, Hao; Yin, Ling; Mao, Liang; Mei, Shujiang; Chen, Tianmu; Liu, Kang; Feng, Shengzhong (Frontiers in Public Health, 2022)
The outbreak of COVID-19 stimulated a new round of discussion on how to deal with respiratory infectious diseases. Influenza viruses have led to several pandemics worldwide. The spatiotemporal characteristics of influenza transmission are not well known, which increases the difficulty of influenza prevention and control. For a long time, influenza prevention and control measures have focused on vaccination of the elderly and children, and school closure. Since the outbreak of COVID-19, the public's awareness of measures such as vaccinations, mask-wearing, and home- quarantine has generally increased in some regions of the world. To control the influenza epidemic and reduce the proportion of infected people with high mortality, the combination of these three measures needs quantitative evaluation based on the spatiotemporal transmission characteristics of influenza in megacities. Given that the agent-based model with both demographic attributes and fine-grained mobility is a key planning tool in deploying intervention strategies, this study proposes a spatially explicit agent-based influenza model for assessing and recommending optimal influenza control schemes. This study considers Shenzhen as the research area. First, a spatially explicit agent-based influenza transmission model was constructed by integrating large-scale individual trajectory data and human response. Then, the model was evaluated across multiple spatial scales based on confirmed influenza case data. Finally, the model was used to evaluate the combined effects of three interventions (vaccinations, mask-wearing, and home-quarantining) under different compliance rates, and optimal combinations were recommended. Research reveals that adults were a high-risk population with a low reporting rate, and children formed the lowest infected proportion and had the highest reporting rate. In addition, this study suggests a combined "V45-M60-Q20" strategy for cities with high vaccination rates and a combined "V35-M60-Q30" strategy for cities with insufficient vaccines. The model and policy recommendations from this study provide a new intervention proposal for influenza epidemic management in the post-COVID-19 era.